Open innovation and performance in the service sector - Ticiana Braga de Vincenzi; Jo\~ao Carlos da Cunha (Innovation & Management Review, 2021)
Purpose - Organizations that decide to invest in innovation must define how this will be done: internally, externally or in a hybrid way, developing internal research and establishing partnerships with other agents of the innovation system. This paper aims to analyze whether the service companies' intensity of openness and innovation efforts are related to their innovative and financial performances. Open innovation assumes that organizations should use external and internal resources as they develop new technologies. Design/methodology/approach - The study used data from the survey of technological innovation (Pintec). As regards innovations, it was considered the commercial and operational innovation performances and the innovative novelty performance. As regards financial performance, it was considered the overall net sales per employee. The intensity of open innovation was measured by the combination of breadth and depth (diversity and importance of the interfaces). The innovative effort was measured by spending on innovation activities. Regressions were applied to evaluate a set of hypotheses. Findings - The results indicate that companies with a greater orientation toward open innovation presented better scores. The results also lead to the conclusion that foreign firm ownership structure and being part of a corporate group were the factors that caused the greatest impact on financial performance in the service sector. Practical implications - The study provides empirical data on the importance of open innovation in improving organizations' performance, especially the breadth of open innovation. Originality/value - The study contributes to expanding the research field addressing the relationship between service innovation and performance.
Keywords: 650; Performance; Open innovation; Service innovation; Survey of technological innovation